الآثار الإدارية لتدخل الشركة القابضة في إدارة الشركات التابعة في القانون الليبي والقانونين المصري والجزائري وموقف الفقه الإسلامي من ذلك - Muneer Ali Abdul Rab; Mohamed Edhir, M.; Mohamed, M. F. (Universiti Sains Islam Malaysia, 2024)
That the subsidiaries, although legally enjoying an independent legal personality and separate financial assets, as well as those companies in formality, their separate governing bodies "General Assembly, Board of Directors" that express their will and defend their interests, but this legal independence is not However, there is a difference between the legislation "Libyan law and the Egyptian and Algerian laws" with regard to the texts regulating the administrative control, and so on. The difference in the administrative effects of the intervention of the holding company in the management of subsidiaries according to each legislation, and the problem of the research raises the interference of the Holding Company to the subsidiary companies controversy in the judiciary and jurisprudence, and this debate is the interpretation of the intervention exercised by the holding company to its subsidiaries, In addition, contemporary legislation has been used to regulate the means of intervention of the holding company in the management of the subsidiary. The aim of the research is that the statement of the intervention of the holding company and its control over its subsidiaries has implications that should be examined, analyzed and studied in the context of Libyan legislation, Egyptian and Algerian legislations, as well as the need to know the position of Islamic jurisprudence. To achieve this objective, the researcher followed the comparative and analytical method to analyze the texts of the provisions of the holding company by the Libyan business law, comparing them with the texts contained in both the Egyptian and Algerian laws, and knowledge of the position of Islamic jurisprudence on them. The researcher concluded that: The administrative control of the holding company of the management of the subsidiary shall deprive the subsidiary company from making any strategic decisions or concluding any agreements or contracts that deviate from the objectives and interests of the holding company. The intervention of the holding company in the management of the subsidiary is permissible in terms of jurisprudence based on the many evidence that requires the satisfaction of the shareholders and that can be deduced through the laws governing the holding company.